Current state and future of 3D bioprinted models for cardio-vascular research and drug development - Liudmila Polonchuk; Carmine Gentile (International Association of Physical Chemists (IAPC), 2021)
In the last decade, 3D bioprinting technology has emerged as an innovative tissue engineering approach for regenerative medicine and drug development. This article aims at providing an overview about the most commonly used bioengineered tissues, focusing on 3D bioprinted cardiac cells and how they have been utilized for drug discovery and development. The review describes that, while this field is still developing, cardiovascular research may benefit from laboratory-engineered heart tissues built of specific cell types with precise 3D architecture mimicking the native cardiac microenvironment. It also describes the role played by regulatory agencies and potential commercialization pathways for direct translation from the bench to the bedside of studies using 3D bioprinted cardiac tissues. ©2021 by the authors. This article is an open-access article distributed under the terms and conditions of the Creative Commons Attribution license (http://creativecommons.org/licenses/by/4.0/).